2019
DOI: 10.21203/rs.2.16028/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new approach to characterize postural deficits in chemotherapy-induced peripheral neuropathy and to analyze postural adaptions after an exercise intervention

Abstract: Background Postural instability presents a common and disabling consequence of chemotherapy-induced peripheral neuropathy (CIPN). However, knowledge about postural behavior of CIPN patients is sparse. With this pilot study, we used a new approach to i) characterize postural impairments as compared to healthy subjects, ii) allocate possible abnormalities to a set of parameters describing sensorimotor function, and iii) evaluate the effects of a balance-based exercise intervention. Methods We analyzed spontaneou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 59 publications
(81 reference statements)
2
15
0
Order By: Relevance
“…confirmed the assumption that poor balance performance in CIPN is related to the impaired interpretation of somatosensory information. In line with their study, we detected abnormally low use of proprioceptive cues in CIPN patients potentially interfering with effective posture control by evaluating perturbed stance and applying a model‐based analysis strategy in a pilot approach 19 . Then, we compared the postural behavior of eight CIPN patients to healthy control participants before and after 12 weeks of intervention (endurance, balance, and strength training).…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…confirmed the assumption that poor balance performance in CIPN is related to the impaired interpretation of somatosensory information. In line with their study, we detected abnormally low use of proprioceptive cues in CIPN patients potentially interfering with effective posture control by evaluating perturbed stance and applying a model‐based analysis strategy in a pilot approach 19 . Then, we compared the postural behavior of eight CIPN patients to healthy control participants before and after 12 weeks of intervention (endurance, balance, and strength training).…”
Section: Introductionsupporting
confidence: 52%
“…Functional impairments and postural instability due to CIPN carry relevant health risks for affected patients 2,4,5,10 . While there are many reports about CIPN‐induced postural instability, 3,5,12,13,21,53 the underlying postural control mechanisms have barely been described 3,11,19,53 —in particular when it comes to characterizing different exercise effects 19 . The aim of the present exploratory study was, therefore, to quantify the exercise effect based on the set of abnormalities derived from comparing the quiet and perturbed stance of patients to healthy control participants via a model‐based analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased visual dependency has been previously observed in cancer patients with CIPN during standing balance. Many postural studies reported a greater increase in postural sway in the absence of vision in cancer patients than that in healthy controls and attributed such changes to CIPN-related somatosensory de cits [22][23][24]. However, the type and location of the somatosensory de cits were often overlooked in these postural studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the type and location of the somatosensory de cits were often overlooked in these postural studies. Kneis et al [24] suggested involvement of proprioceptive dysfunction but did not specify the location of the de cits; others simply attributed the de cits to abnormal sensory symptoms in distal limbs (e.g., feet) without assessing the proximal joints [22,23].…”
Section: Discussionmentioning
confidence: 99%